Offshore oil : are we ready? - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1981)
This film explores the impact of offshore oil in the North Sea by addressing five themes of importance to Newfoundlanders: planning for onshore development, the impact on the rural community, the environment, and the fisheries and the role of government regulations and control.